Dynamics of classroom WTC: Results of a semester study - Mystkowska-Wiertelak, Anna (Studies in Second Language Learning and Teaching, 2016)
The fact that L2 willingness to communicate (WTC) can fluctuate over different time scales is no longer disputed as numerous studies have proved a dynamic rather than trait-like character of the concept (cf. MacIntyre & Legatto, 2011; MacIntyre, Burns, & Jessome, 2011; Mystkowska-Wiertelak & Pawlak, 2014). The changes in the intensity of L2 learners’ readiness to engage in communication in the classroom context have been investigated in a number of studies attempting also to establish factors capable of stimulating or hindering WTC (e.g., Cao & Philip, 2006; Pawlak & Mystkowska-Wiertelak, 2015; Peng, 2014). Many of empirical explorations of L2 learners’ WTC, although representing the ecological perspective, provide solely a snapshot of classroom reality, thus generating a question if such one-at-a-time picture frame can sufficiently accommodate diverse factors that impinge on learners’ readiness to engage in communication. The application of a longitudinal design was thus dictated by the author’s intention to gather information on WTC ebbs and flows not only during single lessons but also continuing over a number of lessons conducted throughout a semester of study, which allowed for exploring a wider spectrum of conditions that affect WTC of advanced learners of English attending speaking classes. Detailed lesson plans, interview and questionnaire data were used to interpret WTC fluctuations reported by the participants at 5-min intervals in the course of 7 lessons. Qualitative and quantitative analysis of the data revealed that the intensity of communicative behaviour depends on an intricate interplay of personal and group-related factors, with a special role ascribed to the instructor whose knowledge of the group characteristics and needs coupled with didactic skills can greatly contribute to increasing WTC in the classroom.